The giant yo-yo mystery - Warner, Gertrude Chandler, 1890-1979.; Papp, Robert (Morton Grove, Ill. : Albert Whitman, 2006)
When the Aldens help a friend of their grandfather$1 (Bs to build the world$1 (Bs largest yo-yo, they soon discover that more than one person is trying to prevent them from finishing the job--and for more than one reason.s
Keywords: Yo-yos -- Fiction; World records -- Fiction; Brothers and sisters -- Fiction; Orphans -- Fiction; Mystery and detective stories